Identification of novel N-terminal splice variants in the DCM-associated gene RBM20. (10th June 2022) - Gaertner, A; Brodehl, A; Sielemann, K; Knoll, R; Gummert, J; Milting, H
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Erich und Hanna Klessmann Foundation Introduction: Mutations in human RBM20, encoding the RNA binding protein 20, cause dilated cardiomyopathy (DCM). Within the nucleus RBM20 partially colocalies with other splicing factors. Sequencing of the cardiac transcriptome of a RBM20-deficient rat model revealed RBM20-dependent regulation of myocardial alternative splicing. We identified several carriers of RBM20 mutations. In the literature, it is postulated that in myocardial tissue only one cardiac form of RBM20 with transcription start in exon 2 is expressed. However, it remains unclear why in the heart this alternative start codon is used. Furthermore, the function of putative different transcripts is unknown. Methods: We analyzed human myocardial cDNA by 5'RACE to identify novel 5'-terminal RBM20 transcripts using gene specific primers within exon 2. Furthermore, we performed RNA-Seq analysis to detect different RBM20 transcripts directly in the human heart. Results: By 5'RACE we could identify additional RBM20 exons localized within the first intron. The usage of two of these exons (internal exons, IE1 and IE2) instead of exon 1 results in transcripts with translation starting in the second exon. The usage of the third alternative internal exon (IE3) might result in a protein differing from full length and cardiac RBM20. Furthermore, we identified transcripts using an alternative exon, which is localized upstream of exon 1. In addition, a transcript comprising exon 1 and 2 of RBM20 was also detected by 5' RACE. Using RNA-Seq we verified the expression of the transcripts containing exon 1, IE1 and IE2 in the human heart, respectively. Conclusions: Here, we present first data on different N-terminal RBM20 transcripts in the human myocardium. In contrast to previous assumptions we identified different splicing forms of RBM20 with unknown functional impact in the human heart. As RBM20 is a DCM-associated gene, the function of the different RBM20 splicing variants might be interesting with respect to cardiomyopathies.